THE IMPACT OF THE MANAGERS' EDUCATIONAL LEVEL ON THE DEVELOPMENT OF THE KNOWLEDGE-BASED ORGANIZATIONS: THE CASE OF INSURANCE COMPANIES IN CROATIA (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
The key objective of the scientific research paper is to identify the key factors of knowledge management that have a direct impact on the economic growth of the national economy within the framework of the European Union. Analyzing named variables through the implementation of primary research in the insurance sector (insurance companies) to create a model of competitiveness in terms of the knowledge economy based on the above research and proven hypotheses in research conducted. Through the analysis of the results is necessary to determine the most important groups of variables that affect the economic growth and competitive advantage. Setting the research is based on three key variables: education, knowledge and human resources. By analyzing the results of research will be determined statistically significant association between elements of the aforementioned variables, and will analyze the mutual influence of key variables on the competitive advantage of the observed insurance companies.Keywords: management, education, knowledge, insurance, Croatia